Part 2: Learning to Communicate About Science: Writing About (Science) Writing and the First-Year Writing Requirement - David Gerstle; Sarah Seeley; Marc Laflamme (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
Part 2: Learning to Communicate About Science: Writing About (Science) Writing and the First-Year Writing Requirement